From science to art and back again: the pendulum of an anthropologist. (2nd October 2018) - Ingold, Tim
ABSTRACT: In this article, I look back over four decades of my career as a professional anthropologist, starting with an orientation that was heavily weighted towards the natural sciences, and ending in a project that seeks to integrate anthropology with the practices of art, architecture and design. This was also a period during which science increasingly lost its ecological bearings, while the arts increasingly gained them. Tracing the journey in my own teaching and research, I show how the literary reference points changed, from foundational texts in human and animal ecology, now largely forgotten, through attempts to marry the social and the ecological inspired by the Marxian revival, to contemporary writing on post-humanism and the conditions of the Anthropocene. For me this has been an Odyssey – a journey home – to the kind of science imbibed in childhood, as the son of a prominent mycologist. This was a science grounded in tacit wonder at the exquisite beauty of the natural world, and in silent gratitude for what we owe to this world for our existence. Today's science, however, has turned wonder and gratitude into commodities. They no longer guide its practices, but are rather invoked to advertise its results. The goals of science are modelling, prediction and control. Is that why, more and more, we turn to art to rediscover the humility that science has lost?